Promoting Mealtime Independence and Mealtime Experience for Individuals With Dementia: A Study Protocol - Zhoumei Yan; Victoria Traynor; Ibrahim Alananzeh; Peta Drury (Nursing Open)
ABSTRACT Background Difficulties in eating can profoundly influence the well‐being of those living with dementia. Previous research has shown that Spaced Retrieval and Montessori‐based interventions can enhance eating independence during meals and optimise nutritional health in people living with dementia in nursing homes. However, few studies examine the effects of these interventions on those living with dementia who follow western‐style eating etiquette. Aim This pilot study aims to evaluate the effectiveness of the SPREMON (Spaced Retrieval and Montessori‐based activities) mealtime intervention on mealtime independence, mealtime engagement and affect (mood), and nutritional status among people living with dementia in a nursing home. Method This quasi‐experimental study will involve people with dementia living in nursing homes. The intervention consists of Spaced Retrieval and Montessori‐based activities designed to enhance eating procedural memory and eating motor skills over 7 weeks. Data will be collected pre‐intervention and post‐intervention and at 3‐month follow‐up. Depending on the distribution of the data, an ANOVA or Friedman test will be used to examine the differences in the means for mealtime independence, engagement and affect, and nutritional status over time. Discussion There is limited evidence of the impact of Spaced Retrieval and Montessori‐based activities in people living with dementia using western dining etiquette. This study bridges this knowledge gap and provides new knowledge about the effectiveness of such interventions to enhance mealtime independence and engagement and affect for people with dementia living in nursing homes. Trial Registration ANZCTR identifier: ACTRN12623001031651p